Improved Ability to Convert News Texts into Dialogue Forms with the Cooperative Integrated Reading and Composition (CIRC) Learning Model for Class IX Students of Berastagi Methodist Middle School in the 2020/2021 Academic Year - Rinta Sari Tarigan (Indonesian Journal of Education and Mathematical Science, 2022)
This study discusses the problems faced by grade IX studentsat SMP Methodist Berastagi.This study aims to improve students' ability to convert news texts into dialogue with theCooperative Integrated Reading and Composition (CIRC)learning modelin class IX students of SMP Methodist Berastagi in the 2020/2021 academic year.This research is a Classroom Action Research (PTK).The subjects ofthisstudywere 35 students of grade IX at SMP Methodist Berastagi in the odd semester of the 2020/2021 academic year.From the results of the analysis, it appears that using theCooperative Integrated Reading and Composition (CIRC)learning model To improve students' ability to convert news texts into dialogues, there was a significant change compared to before using the model.Based on these results it can be concluded that the use of theCooperative Integrated Reading and Composition (CIRC)learning model in solving the problems faced by these students is an effective way to improve student abilities.